Preliminary Study On Phaeomeria sp Economic Potency - Hanifa Marisa; Rahmiwati Rahmiwati; Hidayatullah Hidayatullah (Faculty of Mathtmatics and Natural Sciences, 2010)
Experiment to show influence of Phaeomeria sp rhizome extract treatment to germantion of soybean and green peanut had been done at Laboratory of plant ecology, Biology Department, Faculty of Science, University of Sriwijaya, Indralaya, South Sumatera, Indonesia during February 2008. Data analysis shows that Phaeomeria sp had potency on herbicide, ornamental and medicinal plant.